2006
DOI: 10.1007/s10815-006-9029-1
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler ultrasound assessment of follicular vascularity in the early follicular phase and its relationship with outcome of in vitro fertilization

Abstract: Objective : To determine whether ovarian perifollicular blood flow (PFBF) in the early follicular phase (EFP) was associated with treatment outcome. Design : Retrospective longitudinal cohort study. Setting : Tertiary referral centre/university hospital. Patients : Thirty-four women underwent 37 IVF cycles, which resulted in 35 embryo transfers. Interventions : Serial transvaginal scans using power Doppler ultrasound during the follicular phase. Ovarian PFBF of follicles ≥ 5 mm was subjectively assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
(37 reference statements)
1
17
0
1
Order By: Relevance
“…The positive effect of the extent of follicle vascularity on recovery of the oocyte was indicated by a greater increase in percentage of the follicular wall with colour Doppler signals of blood flow and by a decrease in spectral indices (decreased indicesZincreased vascular perfusion) between hours 0 and 26 in the follicles with oocyte recovery than with non-recovery. The greater vascularity of the follicular wall in association with oocyte recovery is a novel finding in cattle and agrees with findings in women (Bhal et al 2001, Du et al 2006, Shrestha et al 2006) and the tendency for a similar finding in mares . Preovulatory follicular vascular involvement in the subsequent in vitro cleavage of the recovered oocytes was indicated by the lower resistance indices (greater increase in vascular perfusion) at hour 26 than hour 0 (interaction) for a vessel of the follicular wall in the cleavage group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The positive effect of the extent of follicle vascularity on recovery of the oocyte was indicated by a greater increase in percentage of the follicular wall with colour Doppler signals of blood flow and by a decrease in spectral indices (decreased indicesZincreased vascular perfusion) between hours 0 and 26 in the follicles with oocyte recovery than with non-recovery. The greater vascularity of the follicular wall in association with oocyte recovery is a novel finding in cattle and agrees with findings in women (Bhal et al 2001, Du et al 2006, Shrestha et al 2006) and the tendency for a similar finding in mares . Preovulatory follicular vascular involvement in the subsequent in vitro cleavage of the recovered oocytes was indicated by the lower resistance indices (greater increase in vascular perfusion) at hour 26 than hour 0 (interaction) for a vessel of the follicular wall in the cleavage group.…”
Section: Discussionsupporting
confidence: 88%
“…Bhal et al (2001) reported that follicle vascularity is a factor in determining the success of pregnancy establishment after intrauterine insemination. Greater blood flow in the wall of the preovulatory follicle also has been associated with improved rates of in vitro fertilisation (IVF) and embryo development (Bhal et al 1999, Coulam et al 1999, Huey et al 1999, Du et al 2006, Shrestha et al 2006. These studies have indicated that colour Doppler ultrasonographic analysis of individual preovulatory follicles for collection of oocytes for IVF in women may favour selection of oocytes with better development and implantation potential of the embryos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follicle vascularity and its effects on fertility had been investigated in mares (Silva et al 2006) and cows (Shrestha et al 2006, Siddiqui et al 2008). Near ovulation, was shown that an extensive vascularity is formed in the follicular wall until the ovulation occurs (Geva & Jaffe 2000, Reisinger et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been able to demonstrate an association between increases in perifollicular blood flow on power Doppler ultrasound [19] and follicular volume on three-dimensional ultrasonography [20] with higher clinical pregnancy rates. It has already been established that as the follicle size enlarges, the follicular blood flow and follicular fluid VEGF concentrations increase significantly [21].…”
Section: Open Accessmentioning
confidence: 99%